2016
DOI: 10.3126/jhm.v8i1.15576
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy Potential in Kathmandu Valley, Nepal

Abstract: Meteorological data such as solar radiation (1975-1984, and 2002-2010) and sunshine duration (1968-2004) were analyzed to study temporal characteristics of solar energy and investigate solar energy potential in Kathmandu valley. Pre-monsoon and post monsoon seasons have higher mean monthly sunshine duration (about 8 hours/day) than summer (about 5 hours/day) and winter (about 7 hours/day) seasons over Kathmandu. Pre-monsoon and monsoon seasons receive solar energy of about 190 Wm-2 and 170 Wm-2 respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The variation of the air temperature and solar radiation is displayed in Figures 4(a) and 4(b). The research conducted by Regmi and Adhikary [26] and Poudyal et al [27] also reported the similar pattern of monthly variation of solar radiation in Kathmandu and Pokhara valley as we observed in Damak. In winter especially in January, February, November, and December, the sunshine hour was higher but the earth received the least solar radiation due to an oblique incident of the sunlight and optically thick low cloud [28]; as a result, the temperature was also low.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The variation of the air temperature and solar radiation is displayed in Figures 4(a) and 4(b). The research conducted by Regmi and Adhikary [26] and Poudyal et al [27] also reported the similar pattern of monthly variation of solar radiation in Kathmandu and Pokhara valley as we observed in Damak. In winter especially in January, February, November, and December, the sunshine hour was higher but the earth received the least solar radiation due to an oblique incident of the sunlight and optically thick low cloud [28]; as a result, the temperature was also low.…”
Section: Resultssupporting
confidence: 88%
“…The sunshine hour is an important factor to determine solar radiation and air temperature. In Kathmandu valley, the sunshine hour is higher (7 hours/day) in the 3 International Journal of Photoenergy winter, premonsoon, and postmonsoon season and least (5 hours/day) in the monsoon season [26]. The data of the Kathmandu valley represents the whole part of Nepal because it is situated in the middle part of Nepal.…”
Section: Resultsmentioning
confidence: 90%
“…After receiving ethical approval from Institutional Review Board, Institute of Medicine [Ref #295(6–11-E)], this cross-sectional observational study was performed between November 2015 – April 2016 and consisted of a total of 81 adult RTRs (> 18 y of age) out of the total 130 RTRs available at the commencement of the study (sampling percentage: 62.3%) following up in the renal transplant outpatient department (OPD) under Nephrology Unit of Department of Internal Medicine, Tribhuvan University Teaching Hospital, Kathmandu (Latitude 27 0 42′ 2.7684" N), Nepal. There is seasonal variation in the mean monthly sunshine duration in this city; Pre-monsoon and post-monsoon seasons have higher mean monthly sunshine duration (about 8 h/day) than summer (about 5 h/day) and winter season (about 7 h/day) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conventional sources of energy like the use of firewood, coal, fossil fuels, and cow dung, usually release more carbon dioxide (CO2), which is a greenhouse gas, into the atmosphere, thus leading to environmental pollution, which in turn, propels the global warming phenomenon. These prevailing problems have urged scholars and researchers to develop clean and renewable sources of energy as an alternative to fossil fuels [3]. Notably, within the context of the Nepalese region, there is a need for such sources of energy in order to attain sustainable development goals as it continues to advance in the Himalayan region.…”
Section: Introductionmentioning
confidence: 99%